KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PENGOLAH IKAN ASIN DI AIR BANGIS 2014-2024 - Ratna Hardana; Meri Erawati; Lisa Husnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the socio-economic life of salted fish processors in Nagari Air Bangis, Pasaman Barat Regency, during the period 2014–2024. The aim is to describe the social dynamics of coastal communities and analyze the contribution of salted fish processing to household welfare. The research employed the historical method, consisting of heuristics, source criticism, interpretation, and historiography. Data were collected from documents, archives, literature, and interviews with salted fish business owners and workers. The findings indicate that salted fish processing plays a central role in fostering solidarity, cooperation, and strong social bonds within the community. The production process involves all family members, including women and youth, thereby strengthening kinship ties and enhancing household economic empowerment. From an economic perspective, the activity provides income to cover basic needs, children’s education, and improvements in quality of life, although earnings remain vulnerable to weather conditions and fluctuating prices. Furthermore, the transition from small household-based activities to organized production units has expanded marketing networks to interregional markets, increasing income and supporting local economic development.